Tingkat Kebugaran Jasmani Mahasiswa Prodi Pendidikan Olahraga - Rumpoko, Satrio Sakti; Jayanti2, Karlina Dwi; Febrianti, Rima; Hakim, Arif Rohman; Sunjoyo, Sunjoyo; Sistiasih6, Vera Septi (Jurnal Porkes, 2022)
Physical fitness is an important physical component and must be possessed by Sports Education students, because most of the courses offered are practical courses. One of the basic physical fitness that must be possessed is cardiorespiratory endurance. The purpose of this study was to determine the level of basic physical fitness of cardiorespiratory endurance students of the FKIP UMS sports education study program batch 2021. To determine the level of a person's cardiorespiratory endurance can be done by measuring maximum oxygen (VO2max) by means of tests and measurements of running MFT (Multistage Fitness Test). This type of research is quantitative descriptive research which is stated in the form of a percentage. The population of this study used all active students of the FKIP UMS Sports Education Study Program batch 2021 totaling 120 students consisting of 105 boys and 15 girls. The results showed that from 120 sports education students there were 10 people or 8% physical fitness level in the very poor category, 17 people or 14% physical fitness level in the less category, 21 people or 18% physical fitness level in the moderate category, 56 people or 47% at the low level. physical fitness is in good category, and there are 16 people or 13% of sports education students who have a physical fitness level in the very good category. Based on the results of this study, it was concluded that the level of basic physical fitness (cardiorespiratory endurance) of the 2021 FKIP UMS sports education students was good. There are 72 people or 60% of the total 120 students are in the good and very good category.